Pigment epithelium-derived factor is associated with necrotic core progression during statin therapy. Issue 2 (March 2015) - Nozue, Tsuyoshi; Yamagishi, Sho-ichi; Hirano, Tsutomu; Yamamoto, Shingo; Tohyama, Shinichi; Fukui, Kazuki; Umezawa, Shigeo; Onishi, Yuko; Kunishima, Tomoyuki; Hibi, Kiyoshi; Terashima, Mitsuyasu; Michishita, Ichiro
Abstract : Objective: Pigment epithelium-derived factor (PEDF) is a potent inhibitor of angiogenesis and an important target molecule for preventing the progression of atherosclerosis. However, the relationship between PEDF and coronary atherosclerosis has not been fully examined. The aim of the present study is to evaluate the effects of statins on serum PEDF levels and the association between PEDF and coronary atherosclerosis. Patients and methods: Coronary atherosclerosis in nonculprit lesions in the vessel of patients undergoing a percutaneous coronary intervention was evaluated using virtual histology intravascular ultrasound in 99 patients during percutaneous coronary intervention and after 8 months of statin therapy. Results: Serum PEDF levels at baseline and at the 8-month follow-up did not differ. A significant decrease in the fibro-fatty component (−0.24 mm 3 /mm, P =0.0003) and increases in the necrotic core (0.13 mm 3 /mm, P =0.02) and dense calcium components (0.11 mm 3 /mm, P <0.0001) were observed during the 8-month statin therapy. On univariate regression analyses, serum PEDF levels ( r =0.291, P =0.004) and unstable angina pectoris ( r =0.203, P =0.04) showed significant positive correlations with the percentage change in necrotic core volume. Multivariate regression analysis showed that serum PEDF level was a significant independent predictor associated with necrotic core progression during statin therapy ( β =0.218, P =0.04). Conclusion: Statin therapy had no effects on serum PEDF levels. Serum PEDF was a useful biomarker for predicting necrotic core progression during statin therapy, and its levels could be elevated as a counter-regulatory response mechanism to protect against necrotic core progression.